Penerapan Evidence Based Practice Head Massage Therapy Terhadap Penurunan Nyeri Kepala - Kairupan, Michelle; Moningka, Violita Cristiana (Yayasan Syalom Cipta Sumikolah, 2025)
The disease that predominantly attacks the elderly population is hypertension. One of the signs and symptoms of hypertension is headache. Pharmacological interventions in patients with hypertension can be in the form of administering antihypertensive drugs, while one of the non-pharmacological interventions can be done with Head Massage therapy. Describes nursing care given to patients with hypertension involving Head Massage therapy to reduce high blood pressure and pain intensity. The method used is a case study. The subjects used were hypertensive patients with headache problems at Panti Werdha Damai Ranomuut. The results of the study with the application of evidence-based nursing head massage therapy carried out for 2 days, found that the level of pain on the first day was on a pain scale of 5, and on the second day decreased to a scale of 1, from the results of the evaluation it was found that head massage therapy was effective in reducing pain levels. The results of the case study showed that the level of pain after being given head massage therapy intervention decreased the level of pain. To all health workers to be able to provide non-pharmacological therapy in the form of head massage therapy and provide education to clients so that they can apply this therapy when they feel pain due to hypertension.